Attention-deficit/hyperactivity disorder and task-related heart rate variability: A systematic review and meta-analysis. (April 2019) - Robe, Andreea; Dobrean, Anca; Cristea, Ioana A.; Păsărelu, Costina R.; Predescu, Elena
Highlights: Heart rate variability (HRV) reflects variability in time between successive heartbeats. This is the first systematic review and meta-analysis on the impact of ADHD on CVC, after a task demand. Task related-HRV is reduced in ADHD children and adolescents compared with healthy controls. The confounding role of medication could not be fully rulled out. Abstract: Background: Research suggests that Attention-Deficit/Hyperactivity Disorder (ADHD) is associated with autonomic nervous system dysregulation, but the findings were mixed. Method: We conducted a literature review and meta-analysis to quantify the effect of ADHD on vagally-mediated heart rate variability (HRV). PsycINFO, PubMed, Web of Science and Scopus, were searched for case-control or cohort studies reporting measures of vagally-mediated HRV, after a task demand, among individuals with ADHD relative to healthy subjects. Results: Thirteen articles comprising a total of 869 patients with ADHD and 909 healthy participants were included. As compared to controls, ADHD patients had reduced vagally-mediated HRV, corresponding to a small effect size ( Hedge's g = 0.20; CI 95% 0.01 to 0.40). Heterogeneity was high (Q (18) = 76.59, p < 0.001; I² = 77%). There was some evidence of small study effects. Task type, respiration rate assessment and associated comorbid disorders were statistically significant moderators. Conclusions: These findings provide evidence for the associations between ADHD and autonomic dysregulation. Future studies addressing HRV reactivity are needed.